Measuring Students' School Motivation - Cathérine Conradty; Franz X. Bogner (MDPI AG, 2022)
Education is supposed to lay the foundation for vocational maturity. However, young people lose their motivation to learn at school instead. Adequate teaching concepts to promote school motivation need to be developed, but efficient tools to evaluate them at the level of school motivation are lacking. For this purpose, we built upon the established Science Motivation measure (SMOT) by reformulating items for a general school motivation scale (SchMOT) and applying it to 281 fifth graders. Since children are active creators and not consumers of knowledge, we consider learning motivation correlated with creativity, as demonstrated by the original motivation questionnaire. A principal component factor analysis with varimax rotation confirmed the hypothetical four-factor structure: self-efficacy, self-determination, intrinsic motivation and grade motivation. Factor loadings ranged from 0.556 to 0.746; cross-loadings never exceeded 0.4. The SEM model of motivation confirmed the factor structure with self-efficacy as the strongest predictor of motivation. The correlation of motivation and creativity revealed the particular importance of self-efficacy. This study has shown its appropriateness in measuring adolescent school motivation. Results emphasised the need for self-efficacy, both as an indicator of conducive teaching and an essential pedagogical goal. Suggestions for creativity-based teaching initiatives that promote school motivation by incorporating self-efficacy are discussed.